Development and performance evaluation of flow-electrode capacitive deionization (FCDI) module featuring spiral-wounded (SW) structures - Hendrajaya, Glenn Lucas; Xue, Wenchao; Thammarat Koottatep; Ghimire, Anish; Global Water & Sanitation Center (GWSC); AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2026)
Flow-electrode capacitive deionization (FCDI) offers significant advantages in continuous desalination; however, conventional plate-and-frame modules face limitations in scalability and packing density. This research introduces a novel Spiral-Wound FCDI (SWFCDI) architecture, developed through three iterative generations (V1, V2, and V3) to optimize hydraulic distribution and spatial efficiency. The V1 prototype identified critical design drawbacks, including geometric imbalances between membrane lengths and high pumping resistance. These were addressed in the V2 and V3 designs by integrating a dual-channel configuration and an upgraded 5-hole multi-port distribution system to ensure uniform slurry dispersion. Experimental evaluation was conducted under a constant voltage of 1.4 V, using a 10% (w/v) carbon loading and a 5 g/L NaCl feed. Results demonstrated that the architectural upgrades successfully expanded the effective area (Aeff) from 45 cmp2 (Bto 105 cmp2(B, achieving a superior packing density of 0.523 cmp-1 (Bthat has 7 to 12-fold improvement over traditional plate-and-frame modules. While V1 exhibited a high initial Average Salt Removal Rate (ASRR) of 1.092 omol/cmp2(B/min, the optimized V3 module was the only configuration to achieve complete desalination (>99.23% SRE) within 160 minutes. Despite these performance gains, the study identified a trade-off in energy efficiency; the Coulombic Efficiency (CE) ranged from 77.7% to 84.8%, primarily due to carbon clogging induced by the internal spacer mesh. Consequently, the specific energy consumption (Ev) reached 3.98 kWh/mp3 (Bfor total salt removal. These findings establish the SWFCDI as a highly compact and potent platform for high-purity water production, while highlighting the necessity for slurry optimized spacers in future iterations to bridge the gap between laboratory-scale prototypes and practical industrial implementation.s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2026
Keywords: Saline water conversion